THE PROCESS AND THE BENEFIT OF GANDAI DANCE FOR TALANG BUAI SOCIALIZE OF SELAGAN RAYA DISTRICT OF MUKOMUKO REGENCY OF BENGKULU PROVINCE - Madeni, Denti Sari (Pendidikan Sosiologi, 2014)
Background of this research is tradition in gandai dance is done by citizen in every wedding ceremony, entertain. Gandai dance is routine activity is done by Talang Buai socialize. This tradition has still done until now, while in another area which is in Selagan Raya district has not done this gandai dance tradition. This research is purpose to describe gandai dance tradition ways and to describe the advantage of gandai dance tradition in Talang Buai town of Selagan Raya district of MukoMuko regency of Bngkulu province. The approach which is used in this research is qualitative approach by descriptive type. Informer of this research is a group that is Talang Buai that is Talang Buai socializes. The selection of informer on this research is using purposive sampling technique; kind of data that used is primer data and secondary data. The collecting technique are observation (non-participant observation), interview, deeply, documentation. The analysis unit is a group. The data analyze is use Miles and Huberman principle which is consist of four step that is: (1) the data collecting, (2) the data reduction, (3) the data and (4) conclusion. Result of this research is to show that the process way of gandai dance tradition of Talang Buai town throw steps are begins from: (a) socialize who become that socialize habit, (b) prepare or gandai dance tradition by preparing of equipment that needed when doing gandai dance: preparing of equipment, preparing of dancer, (c) the next steps is gandai dance tradition way, it held in three places that are: wedding,, and young entertain, (d) people that participated in gandai dance tradition, all of Talang Buai socialize who up age 10 years for participate in this tradition. The benefit of gandai dance tradition for Talang Buai socializes: (1) to increase integration in socialize, (2) to keep solidarity in socialize, (3) gandai dance is use ful to keep value and norm in socialize such as: value, culture, social value, religion value, and moral value.